Penambatan Molekuler α, β, dan γ-mangostin Sebagai Inhibitor α-amilase Pankreas Manusia - Gaspersz, Nelson; Sohilait, Mario Rowan (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2019)
The in silico studies of interactions between the human pancreatic α-amylase (HPA) enzyme to α, β, and γ-mangostin ligands has been carried out using the molecular docking method. Ligands α, β, and γ-mangostin interacting through the formation of hydrogen and van der waals bonds to residues on the enzyme active side. The α-mangostin ligands resulting seven hydrogen and six van der waals bonds with the residues involved were Trp59, Gln63, Trp96, Thr163, Thr164, Ala198, His201, Glu233, and Asp300. β-mangostin resulting five hydrogen and eight van der waals bonds with residues involved were Gln63, Trp96, Thr163, Thr164, Arg195, Asp197, His201, Glu233, Asp300, and His305; while γ-mangostin forms nine hydrogen and five van der waals bonds with residues involved were Trp59, Gln63, Trp96, Thr163, Asp197, Ala198, His201, Glu233, and Asp300. The binding affinity of α, β, and γ-mangostin to the HPA enzyme obtained were -7.0; -6.6; and -7.4 kcal/mol with root mean square deviation (RMSD) value were 1,850; 1,956; and 1,811 Å respectively. Ligand γ-mangostin has potential activity as an inhibitor of HPA enzyme due to the stabilization of the complexes formation with lower binding affinity (validated with RMSD value) when compared to α and β-mangostin.